Reconexão com a saúde integral: Laboratório de Práticas Integrativas e Complementares do Instituto Federal Farroupilha/Campus Júlio de Castilhos - Bueno, Daiane de Fátima dos Santos (2025)
Integrative and Complementary Health Practices (PICS) in Brazil are composed of complex medical systems and therapeutic resources aimed at stimulating the body's natural mechanisms for health recovery, maintenance, and prevention. This dissertation aimed to implement the Laboratory of Integrative and Complementary Practices at the Federal Institute of Education, Science and Technology Farroupilha Campus Júlio de Castilhos-RS (LAPICS-IFFARJC), generating opportunities for access to Integrative and Complementary Health Practices (PICS) through its actions seeking to incorporate the use of these practices into the quality of life of employees. The methodological design was based on a qualitative approach, characterized as applied research, action research. The methodological actions began in December 2023 and continue to the present, directly benefiting more than 400 people, including employees and the external community. As a result of these actions, it was possible to demonstrate that the interventions had satisfactory results in relation to the content covered, as numerous questions and case reports occurred, thus demonstrating interest in the topics addressed and acceptance of Integrative and Complementary Health Practices (PICS). This corroborated the objective of implementing LAPICS-IFFAR-JC. We emphasize that the social impact, as well as the relevance and reach, were significant. LAPICS stands out as an extension program and training center for new therapists, having expanded beyond the municipality of Júlio de Castilhos, reaching the central region of Rio Grande do Sul with its actions. The dissemination and implementation of PICS aims to provide free access to public servants and the community, contributing to the promotion of health and self-care.